Myricetin Suppresses Ovarian Cancer In Vitro by Activating the p38/Sapla Signaling Pathway and Suppressing Intracellular Oxidative Stress - Li, Qi; Tan, Qi; Ma, Yangfei; Gu, Zehui; Chen, Suxian (Frontiers in Oncology, 2022)
Ovarian cancer is a common malignancy with a mortality and effective, efficient treatments are urgently needed. Myricetin (Myr) is a flavonoid with antioxidant and anticancer properties. Here, we assessed Myr’s toxicity on the normal ovarian epithelial cell line, IOSE-80 and the mechanism by which it suppresses proliferation, migration, and invasion of ovarian cancer SKOV3 cells. The effects of Myr on SKOV3 cells were assessed using CCK-8, oxidative stress, wound healing, Transwell, Hoechst 33258 staining, and western blot assays. Our data show that although Myr was not toxic against IOSE-80 cells for a range of concentrations 0-40μM, it suppressed SKOV3 cell proliferation, migration, and invasion and enhanced apoptosis. Mechanistically, it activated the p38/Sapla signaling pathway, thereby inhibiting oxidative stress and reducing the level of ROS in tumor cells. Our data show that Myr suppresses ovarian cancer cells in vitro and suggests Myr as a candidate agent against ovarian cancer.